Neuroimaging in infants who present with inborn errors of metabolism - Gropman, Andrea L. (Journal of Pediatric Biochemistry, 2014)
In the clinical management of inborn errors of metabolism (IEMs) a central focus is on protecting the central nervous system (CNS) from the toxic effects of the metabolic dysfunction. Despite our ability to screen for and detect many of these conditions in the newborn period, making early treatment possible, cognitive abnormalities may still result because of our inability to identify and alter the early steps in brain pathology. A key in preventing neurological imaging is the understanding the steps in the brain injury and the time course of injury in order that physicians may intervene. Since the infant who is comatose does not give us clues as to whether it is due to infection, inborn errors of metabolism and which one, seizures or other causes based on examination alone. Therefore, neuroimaging may provide biomarkers for diagnosis and prognosis. This review will discuss use of neuroimaging in inborn errors of metabolism of acutely ill infants.
Keywords: Central nervous system (CNS); inborn errors of metabolism (IEMs); magnetic resonance imaging (MRI)